LOYALITAS PELANGGAN DI RESTORAN CEPAT SAJI - Putri Agustia; Afrilia Denia; Yoanita Febriyani; Robet Kristaung (PT. Cendekia Sapta Indonesia, 2022)
The purpose of this study is to analyze the effect of service quality and customer satisfaction on customer loyalty, and analyze the effect of service quality on customer satisfaction in the fast restaurant industry, namely McDonald's. A theoretical model, including a hypothesis, has been proposed in this study. The data of this research were collected by using the sampling method. The unit analysis of this research was obtained through questionnaires to 200 respondents who like to buy fast food at McDonald's. This study uses quantitative methods with data collection techniques using Non Probability Sampling with the type of Purposive Sampling technique, and collected as many as 200 respondents. The criteria for respondents are respondents who are consumers of McDonald's fast food restaurants in DKI Jakarta. Factor Loading Analysis, Cronbach's Alpha Analysis, and Structural Equation Modeling (SEM) were used to examine the relationship between variables in the research model with SPSS 25 and AMOS 26. The results showed that Service Quality had a significant positive effect on Customer Satisfaction, Service Quality had an insignificant negative effect. on Customer Loyalty, and Customer Satisfaction have a significant positive effect on Customer Loyalty. This shows that the company's efforts towards service quality and customer satisfaction will increase consumer interest. In addition, when consumers are satisfied with the quality of service obtained, consumers will tend to be loyal to the company. This can be achieved by improving public facilities and the quality of services provided by employees. Tujuan penelitian ini untuk menganalisis pengaruh service quality dan customer satisfaction terhadap customer loyalty, dan menganalisis pengaruh service quality terhadap customer satisfaction pada industri restoran cepat saji yaitu McDonald’s. Sebuah model teoritis, termasuk hipotesis, telah diusulkan dalam penelitian ini. Data penelitian ini dikumpulkan dengan menggunakan metode sampling. Unit analisis penelitian ini diperoleh melalui kuesioner kepada 200 responden yang gemar membeli makanan cepat saji di McDonald’s. Studi ini menggunakan metode kuantitatif dengan teknik pengumpulan data menggunakan Non Probability Sampling dengan jenis teknik Purposive Sampling, dan terkumpul sebanyak 200 responden. Kriteria responden adalah responden yang merupakan konsumen dari restoran cepat saji McDonald's di DKI Jakarta. Analysis Factor Loading, analysis Cronbach’s Alpha, dan Structural Equation Modeling (SEM) digunakan untuk menguji hubungan antar variabel dalam model penelitian dengan SPSS 25 dan AMOS 26. Hasil penelitian menunjukkan bahwa Service Quality berpengaruh positif signifikan terhadap Customer Satisfaction, Service Quality berpengaruh negatif tidak signifikan terhadap Customer Loyalty, dan Customer Satisfaction berpengaruh positif signifikan terhadap Customer Loyalty. Ini menunjukkan bahwa upaya perusahaan terhadap service quality dan customer satisfaction akan meningkatkan minat konsumen. Selain itu, ketika konsumen merasa puas dengan kualitas pelayanan yang didapatkan, konsumen akan cenderung loyal terhadap perusahaan. Hal ini dapat diraih dengan meningkatkan fasilitas umum dan kualitas pelayanan yang diberikan oleh karyawan.